Effects of Covid-19 on the purchasing behavior of Generation Z, a study in Ecuador, Mexico and Colombia (2021)
The purpose of this research is to know the effects that these sanitary emergency measures by the SARS-Cov-2 virus caused in the consumption behavior of Generation Z (born between 1994-2010), through the measurement of variables related to personal, social, psychological and cultural factors. A quantitative investigation was carried a consumers or Ecuador México y Colombia, building a Structural Equation Model (SEM) made up of five constructs and twenty-three indicators that explain these effects. The results show that the relationships between consumer behavior and personal, social and cultural factors are significantly associated, providing some guidelines for establishing marketing strategies and meeting the needs of this population in times of crisis better.